Waste paper in Early Modern England privy tokens - Reynolds, Anna (Oxford University Press, 2024)
"'Waste Paper in Early Modern England' argues that rhetorical commonplaces referring to waste paper are indicative of everyday, material experience - of an author's, reader's, housewife's, or city-dweller's immersion in an environment brimming with repurposed scraps and sheets."
Literaturverzeichnis Seite 200-222
Titel der Dissertation: Privy tokens: waste paper in Early Modern England, 1536-1680
Keywords: Geschichte 1500-1800; Kultur; Altpapier; Papierabfall; England; Waste paper / History / England; Waste paper / Recycling / History / England; Environment and Ecology; The environment; Hochschulschrift